Reduction of Quinones by NADH Catalyzed by Organoiridium Complexes - Liu, Zhe; Deeth, Robert J.; Butler, Jennifer S.; Habtemariam, Abraha; Newton, Mark E.; Sadler, Peter J. (Angewandte Chemie International Edition, 2013)
One electron at a time: Half‐sandwich organometallic cyclopentadienyl–IrIII complexes containing N,N‐chelated ligands can catalyze the reduction of quinones (Q), such as vitamin K3, to semiquinones (Q.−) by coenzyme NADH (see picture). DFT calculations suggest that the mechanism involves hydride transfer followed by two one‐electron transfers and the unusual IrII oxidation state as a key transient intermediate.